2008
DOI: 10.1111/j.1365-2966.2008.13533.x
|View full text |Cite
|
Sign up to set email alerts
|

Be phenomenon in open clusters: results from a survey of emission-line stars in young open clusters

Abstract: Emission‐line stars in young open clusters are identified to study their properties, as a function of age, spectral type and evolutionary state. 207 open star clusters were observed using the slitless spectroscopy method and 157 emission stars were identified in 42 clusters. We have found 54 new emission‐line stars in 24 open clusters, out of which 19 clusters are found to house emission stars for the first time. About 20 per cent clusters harbour emission stars. The fraction of clusters housing emission stars… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(111 citation statements)
references
References 79 publications
7
103
1
Order By: Relevance
“…Figure 12 presents the percentages per spectral subclass, referred to the total sample of Be stars, but separately for SMC and Galaxy. The Galactic data are from , McSwain & Gies (2005), and Mathew et al (2008). The distributions for the two galaxies are similar but the incompleteness of the SMC data becomes apparent beyond B2 (cf.…”
Section: The Be Phenomenon: Smc Vs Galaxymentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 12 presents the percentages per spectral subclass, referred to the total sample of Be stars, but separately for SMC and Galaxy. The Galactic data are from , McSwain & Gies (2005), and Mathew et al (2008). The distributions for the two galaxies are similar but the incompleteness of the SMC data becomes apparent beyond B2 (cf.…”
Section: The Be Phenomenon: Smc Vs Galaxymentioning
confidence: 99%
“…6 .0 -6 .3 6 .3 -6 .6 6 .6 -6 .9 6 .9 -7 .2 7 .2 -7 .5 7 .5 -7 . Mathew et al (2008), there seems to be a decrease first in the number of open clusters with Be stars towards 30-40 Myr (log (age) = 7.5-7.6). Thereafter, there is an increase during the evolution, and another decrease after 50-60 Myr (log (age) = 7.7-7.8).…”
Section: The Be Phenomenon: Smc Vs Galaxymentioning
confidence: 99%
“…More recent surveys of Be stars in galactic open clusters and OB associations concluded that stars in these environments also show spectroscopic and photometric irregular variations (McSwain & Gies 2005;Mathew, Subramaniam, & Bhatt 2008). These photometric variations have been observed in three time-scales that are often superimposed: (1) The short-term variations with time-scales from hours to days and amplitudes up to 0.1 mag, are probably caused by nonradial pulsations or rotation (Percy et al 2002;Percy, Harlow, & Wu 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Currie et al (2008) excess, implying that these CBe stars are just in the beginning of the dust formation. Recently, Mathew et al (2008) claimed to have identified a CBe star in IC 1590 which is only ∼ 4 Myr old, marking the nature of CBe stars even more puzzling ever. …”
Section: Dust Formation Of Evolved Be Starsmentioning
confidence: 99%